A long-term retrospective analysis of oncologic and fertility outcomes in cervical cancer patients undergoing radical trachelectomy - Liu, Yu; Zhang, Xuyin; Xin, Weijuan; Ding, Yan; Zhang, Yunqiang; Zhang, Ning; Hua, Keqin (Frontiers in Oncology, 2025)
BackgroundGiven the excellent prognosis of early-stage cervical cancer, fertility-sparing surgery has grown as a priority, significant alternative for radical hysterectomy in women being of reproductive age. We aimed to investigate the outcomes and subsequent pregnancies of early-stage cervical cancer patients who received radical trachelectomy. Moreover, there is a scarcity of literature directly comparing the impact of whether performing cervical cerclage concurrently with radical trachelectomy on patients’ reproductive outcomes.MethodsWomen with IA1-IB2 cervical cancer who underwent fertility-sparing surgery at the Obstetrics and Gynecology Hospital of Fudan University were reviewed from January 2014 to May 2024.Radical trachelectomy in 70 women was performed by surgical team from the gynecologic oncologic center. Clinical characteristics, intraoperative, pathological results, oncologic, fertility and follow-up data of these patients were recorded and retrospectively analyzed. This study compared surgical and perinatal outcomes between patients who underwent cervical cerclage during radical trachelectomy (n=49) and those who did not receive the procedure simultaneously (n=21).ResultsA total of 70 women (mean age: 31years) underwent radical trachelectomy (RT) of whom 68.6% were nulliparous. The FIGO stage distribution was IA1 (n=6), stage IA2 (n=7), stage IB1 (n=49), and stage IB2 (n=8). The operative duration was significantly longer in the cerclage group than in the control group (285.4±63.9 min vs 204.8±61.9 min; p < 0.001, 95% CI 47.51-113.48) with greater intraoperative blood loss (201.0 mL vs 170.1 mL, p=0.187, 95% CI -15.10-75.72). Overall, 36 women (51.4%) were seeking parenthood, and 26 succeeded (72.2%). There were 20 live births (76.9%), 12 women delivered in term (46.2%), 7 infants were born between 32 and 36+6 weeks, 1 between 28 and 31+6 weeks, all live birth. The mean neonatal birth weight was slightly lower in the cerclage group than in the control group (2625 g vs 2828.6 g; p=0.265, 95% CI -575.17 to 168.03). At the end of the follow-up period (median 68.7 months, range 34–153 months), one individual is currently 27+3 weeks pregnant, three patient had recurrence, and all women are alive and 20 children born to fertility-sparing surgery patients exhibited normal development.ConclusionRadical trachelectomy provides excellent oncologic results with an outstanding fertility rate and obstetric outcome for patients with early cervical cancer. RT combined with intrauterine-cervical stent is a safe and effective fertility-sparing surgery but cervical cerclage is not recommended.